Public Relations Marketing Strategy of SMP Negeri 4 Surakarta in Maintaining Good Communication with Stakeholders - Zon Vanel; Lina Sinatra Wijaya; George Nicholas Huwae (Master of Management, School of Business and Management, Petra Christian University, 2024)
This study aims to find out the marketing strategy of the SMP Negri 4 Surakarta in maintaining good communication with the stakeholders. This descriptive qualitative research uses interviews and observations to gain the data. This research is also exploratory because it seeks to explore the right multimedia-based public relations strategy for managing information media at SMP Negeri 4 of Surakarta. Field findings show that a lack of human resource literacy in managing school information media causes problems in the less-than-optimal organizational system or management of school information media. Based on the first year of research findings, the Inflorescence Model describes the flow of school information media management. The researchers use purposive sampling to pick individuals who are knowledgeable about SMP Negeri 4 Surakarta's marketing strategy, digital media management, and public relations. School administrators, instructors, public relations officers, and other relevant stakeholders may be included. Researchers transcribed interviews, organized observation notes, and documented data before identifying reoccurring themes and patterns in the data. Researchers will code the data by methodically identifying and categorizing information relevant to the research aims. Researchers will examine the data after it has been coded, looking for relationships, connections, and insights. To assure the legitimacy and integrity of the outcomes, researchers may compare findings from different participants and data sources. The analysis's findings will be reported in a research paper or report arranged around main themes, findings, and conclusions. The result of this study is that the marketing public relations strategies in maintaining good communication with its stakeholders are preparing modules for teachers, school managers, and readers to build, develop, and promote the management of structured digital-based school media and fostering literacy rates in schools. Another strategy step is to implement an evaluation system from the information media to identify existing deficiencies and make improvements in the future. Push, Pull, and Pass strategy approaches and digital marketing tools are also used to implement the strategy and maintain good stakeholder communication.